Study on Dynamic Performance of Standard Sand Based on KTL Dynamic Triaxial Apparatus - Bo Li; Xiaofei Li; Xueyang Xing (Shock and Vibration)
The determination of dynamic properties is of great scientific significance to the constitutive modeling and parameter determination of large deformation for sand liquefaction. For Fujian standard sand, a new high-precision KTL bidirectional dynamic triaxial test system was used to carry out liquefaction tests under equal consolidation and different equal amplitude cyclic stresses. The dynamic characteristics of Fujian standard sand, such as dynamic stress and dynamic strain test results, pore water pressure model, effective stress path, and stress-strain relationship curve, were studied. The main results are as follows: the whole vibration process of the sample could be basically divided into four stages: the greater the dynamic stress is, the easier the sample is to liquefy. With the increasing vibration times, the samples under different dynamic stress amplitudes meet the qualitative analysis of the first three stages of liquefaction; that is, the pore water pressure increases rapidly at the beginning of vibration, and the growth is stable in the middle stage. When the effective pore water pressure increases to 60 kPa, it begins to increase sharply and finally reaches the effective confining pressure, and then, the soil sample liquefies. The axial strain begins to accumulate in the compression direction and gradually increases. After liquefaction, the strain accumulates in the tensile direction in equal amplitude. During the whole vibration process, the axial strain of the sample can develop greatly in the tensile and compressive direction. Under the action of different cyclic stresses, the stress path of the soil sample tends to zero, and the rate of effective stress state varies greatly, indicating that the dynamic stress has a great influence on the dynamic liquefaction process of Fujian standard sand. In the dynamic triaxial test of standard sand, the difference in dynamic stress amplitude will lead to great changes in the stress-strain relationship curve. But it has little effect on the analysis of liquefaction dynamic characteristics of sand.